Efektivitas Pemberian Terapi Massage Terhadap Penurunan Low Back Pain - Putri Rahmadini; Liza; Donal Syafrianto; hastria Efendi (Jurnal IKEOR, 2025)
Low back pain is a common complaint of lower back pain experienced by active individuals, including students at the Faculty of Sport Science. This condition can be caused by repetitive physical activity, poor posture, and prolonged muscle tension. This study aimed to determine the effectiveness of massage therapy in reducing myogenic LBP pain in female students at the Faculty of Sports and Sports Medicine, Universitas Negeri Padang. The study used a one-group pretest-posttest design, with 11 respondents selected using purposive sampling. Massage therapy, using effleurage, friction, and tapotement techniques, was administered for 10 minutes each session, five times over two weeks. Pain levels were measured using a Visual Analog Scale (VAS) before and after treatment. Data were analyzed using a paired-sample t-test at a 5% significance level. The results showed an average pain score before treatment of 7.18 ± 1.25 and after treatment of 3.36 ± 0.67. Statistical tests yielded a p-value <0.05, indicating a significant difference between pain scores before and after therapy. Regular massage therapy effectively reduced myogenic LBP pain levels in students. This therapy can be an easy-to-implement non-pharmacological treatment alternative to reduce lower back pain.